MicroRNAs as biomarkers in glaucoma and potential therapeutic targets - Bridget Martinez; Philip V Peplow (Neural Regeneration Research, 2022)
Glaucoma is a neurodegenerative disease in which optic nerve damage and visual field defects occur. It is a leading cause of irreversible blindness. Its pathogenesis is largely unknown although several risk factors have been identified, with an increase in intraocular pressure being the main one. Lowering of intraocular pressure is the only treatment available. Open-angle glaucoma is the most common form of the condition, accounting for ~90% of all cases of glaucoma, with primary open-angle glaucoma and exfoliation glaucoma being the most frequent types. There are strong indications that microRNAs play important roles in the pathogenesis of primary open-angle glaucoma. Most of the recent studies reviewed had performed microRNA profiling in aqueous humor from glaucoma patients compared to controls who were chiefly cataract patients. A very large number of microRNAs were dysregulated but with limited overlap between individual studies. MiRNAs in aqueous humor that could be possible targets for therapeutic intervention are miR-143-3p, miR-125b-5p, and miR-1260b. No overlap of findings occurred within the dysregulated miRNAs for blood plasma, blood serum, peripheral blood mononuclear cells, and tears of primary open-angle glaucoma patients. Several important limitations were identified in these studies. Further studies are warranted of microRNA expression in aqueous humor and blood samples of primary open-angle glaucoma patients in the early stages of the disease so that validated biomarkers can be identified and treatment initiated. In addition, whether modifying the levels of specific microRNAs in aqueous humor or tears has a beneficial effect on intraocular pressure and ophthalmic examination of the eyes should be investigated using suitable animal models of glaucoma.